Fertilizer use patterns in Yunnan Province, China: implications for agricultural and environmental policy - Yunju L; Kahrl F; Jianjun P; Roland-Holst, D.; Yufang S; Wilkes, Andreas; Jianchu X (Elsevier, 2012)
Balancing the need to increase crop yields with the need to reduce the environmental impacts of fertilizers will pose major policy, regulatory, and extension challenges for China. A growing number of studies have demonstrated the potential for improving fertilizer use efficiency in China, but it is not clear how to achieve these efficiency improvements on a larger scale. The empirical foundation for fertilizer policy in China is still weak, particularly in inland provinces. This paper examines fertilizer use patterns in Yunnan Province, an inland and ecologically important province in Southwest China, drawing on two household surveys. We find that fertilizer application rates in the survey areas are highly heterogeneous, among crops, households, and regions. Managing this diversity poses the largest challenge to fertilizer policy in Yunnan and, by extension, in China. None of the factors that we examine in this study are robust predictors of fertilizer intensity (kg ha−1) in the survey regions, though in one survey there is a strong inverse relationship between farm size and fertilizer intensity. The lack of clearer signals in the survey data, a consequence of heterogeneity in cropping patterns, agroecosystems, and local economies, underscores the importance of locally tailored approaches to fertilizer regulation in China, and of a strong, service-oriented agricultural extension system oriented around sustainable agriculture.